Engineering Mechanics 2 - Gross, Dietmar; Hauger, Werner; Schröder, Jörg; Wall, Wolfgang A.; Bonet, Javier (Springer, 2011)
Mechanics of Materials is the second volume of a three-volume textbook on Engineering Mechanics. Volume 1 deals with Statics while Volume 3 contains Dynamics. The original German version of this series is the bestselling textbook on Engineering Mechanics in German speaking countries; its 13th edition is currently being published. It is our intention to present to engineering students the basic concepts and principles of mechanics in the clearest and simplest form possible. A major objective of this book is to help the students to develop problem solving skills in a systematic manner. The book has been developed from the many years of teaching experience gained by the authors while giving courses on engineering mechanics to students of mechanical, civil and electrical engineering. The contents of the book correspond to the topics normally covered in courses on basic engineering mechanics, also known in some countries as strength of materials, at universities and colleges. The theory is presented in as simple a form as the subject allows without becoming imprecise. This approach makes the text accessible to students from different disciplines and allows for their different educational backgrounds. Another aim of the book is to provide students as well as practising engineers with a solid foundation to help them bridge the gaps between undergraduate studies and advanced courses on mechanics and practical engineering problems. A thorough understanding of the theory cannot be acquired by merely studying textbooks. The application of the seemingly simple theory to actual engineering problems can be mastered only if the student takes an active part in solving the numerous examples in this book. It is recommended that the reader tries to solve the problems independently without resorting to the given solutions. In order to focus on the fundamental aspects of how the theory is applied, we deliberately placed no emphasis on numerical solutions and numerical results.
Mechanics of Materials